The Imperative for Justiciability of Economic, Social, and Cultural Rights in Post-Civil War Sri Lanka - Sarvananthan, M.; Sivakaran, N. (Journal of Law, Social Justice & Global Development, University of Warwick, UK, 2023)
Between 2015 and 2019 Sri Lanka has been in the process of drafting a new Constitution in the aftermath of the civil war that lasted from 1983 to 2009. In spite of the very high human development in Sri Lanka, public expenditures on education and health as a proportion of the GDP have declined since the 1960s. Besides, it is argued that democracy in Sri Lanka is patronage cum greed based, and hence a case is made for inculcating a merit cum need based democracy for which justiciability of Economic, Social, and Cultural Rights (ESCR) is a sine qua non. Moreover, we argue a case for incorporating ESCR as justiciable rights in the proposed new Constitution not only on its own right but also as a means of durable peace-building in the aftermath of a savage civil war
Keywords: ESCR; Human Rights; Peace-building; Rights based Development; Sri Lanka; Transitional Justice